Use of fly Ash a Substitute For Part Cement In Wall Plaster: An Effective Study on The Quality Tests of Plastering - Azizah Wardani; Sutria Desman; Fatma Ira Wahyuni (Fakultas Teknik Sipil dan Perencanaan, 2025)
Cement production in the construction industry generates a significant amount of carbon dioxide (CO2) emissions, which negatively impact the environment. One of the efforts to reduce this impact is by utilizing coal combustion waste (fly ash) as a partial replacement for cement. This study aims to determine the effect of using fly ash on the compressive strength of wall plaster and to identify the optimum percentage of fly ash substitution that still meets plaster quality standards. The research method used was a laboratory experiment with a quantitative approach. The variations of fly ash used were 20%, 30%, and 40% of the cement weight. Test specimens were cube - shaped with dimensions of 5 x 5 x 5 cm, and compressive strength tests were conducted at 7 and 21 days. The fly ash used in this study was obtained from the Sawah Lunto stream power plant PLTU Sawah Lunto). The results showed that the addition of fly ash affected the mechanical properties of the plaster, particularly its compressive strength. The highest compressive strength value was obtained from the mixture containing 20% fly ash, reaching 18.24 Mpa at 28 days of age.